Exploring the complementary relationship between solar and hydro energy harvesting for self-powered water monitoring in low-light conditions. (June 2021) - Maghami, Iman; Sobral, Victor A.L.; Morsy, Mohamed M.; Lach, John C.; Goodall, Jonathan L.
Abstract: Relying on solar energy alone to power water monitoring stations limits the ability to monitor water resources in low-light locations, such as for streams with dense tree canopy cover. To address this limitation, water monitoring stations could have a supplementary micro hydro-turbine to harvest kinetic energy from streamflow. To explore this possibility, we simulated the energy harvesting potential at 42 locations with long term stream velocity records and determined the canopy cover for streams across the contiguous United States (CONUS). Results show that a site with typical streamflow velocity and dense evergreen tree canopy would have 1.6 times less sample loss, from 68% to 43%, after adding hydro energy harvesters. Many streams across the CONUS with dense canopy cover could benefit from this, especially headwater streams and streams in the Southeastern US where many watersheds have more than 50% of their stream length under dense tree canopy cover. Highlights: Hydro energy harvesting could enable more ubiquitous monitoring of water resources. Hydro power complements solar power by lowering the variance in harvested energy. Hydro energy harvesting can exceed solar power when dense tree canopy is present. In the Southeastern US, as much as 58% of water bodies have dense tree canopy. In the contiguous US, first through fourth order streams have 32% mean tree canopy.